The Role of Cepagan Village Weaving in the Development of the Creative Economy in Warungasem District - Mutiara Bintang; Muhamad Wildan; Muhamad sakdullah (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
This study examines the role of Cepagan Village weaving in the development of the creative economy in Warungasem District, Batang Regency, Central Java. Using a qualitative approach and case study design, this study explores the economic and social contributions of the weaving industry, the challenges faced, and development strategies in the context of the creative economy. The results of the study show that Cepagan weaving plays an important role in cultural heritage preservation, product innovation, and cross-sector collaboration. This industry has a significant impact on job creation, increasing regional income, and economic multiplier effects. However, challenges such as competition with modern products, regeneration of artisans, and limited market access need to be overcome. Development opportunities through digitalization, ecotourism, and collaboration with the fashion industry open up new prospects for the sustainability of the weaving industry. This research provides valuable insights into the integration of traditional crafts into the modern creative economy and can be a reference for the development of local wisdom-based community empowerment policies and programs.